STUDI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM AQUA DI KOTA SURAKARTA - Moech Nasir (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2008)
This Research analyse consumer purchasing decision of drinking water AQUA at Surakarta City. Internal issue Formulation this research is what productquality, price, and promotion by parsial have an influence consumer purchasing decision of drinking water AQUA at Surakarta City?, and what product quality, price, and promotion by simultan have an inflluence consumer purchasing decision of drinking water AQUA at Surakarta City? This Research aim toanalyse the influence by parsial, product quality, price, and promotion to consumer purchasing decision of drinking water AQUA at Surakarta City and also to analyse the influence by simultan, product quality, price, and promotion to consumer purchasing decision of drinking water AQUA at Surakarta City.Population in this research is consumer doing purchasing of drinking waterAQUA at Surakarta City, sampel taken by as much 100 responder with thetechnique of sampling is convenience sampling. Technique of data collecting use the questioner while technique analyse the data use the doubled linear analysis regresi. Result of analysis indicate that the product quality (X1) and promotion (X3) have the influence of positip and significan to consumer purchasing decision of drinking water aqua, while price (X2) have the influence which negatif and is not significant to consumer purchasing decision of drinking water aqua. Here in after see the level of value of coefficient regresi from third known that the independent variables that variable of product quality have larger ones influence compared to variable of price and promotion for consumer purchasing decision and this means variable of product quality (X1) own the biggest contribution compared by variable of price and promotion. Then pursuant to result of significance test known that the variable of product quality have the influence which significan to consumer purchasing decision. This matter is supported from value assess the t count (8,002) t table (1,96), price variable have the influence negatip and is not significan to consumer decision. This matter is supported from value assess the t count (- 0,088) t table (- 1,96), and promotion variable have the influence of positip and significan to consumer purchasing decision. This matter is supported from value assess the t count (2,432 t table (1,96). From other sideing that result of analysis indicate that the product quality, price and promotion by together have the influence which significant to consumer purchasing decision. This matter is supported from value Fcount (47,239) F table(2,76). Then from analysis of coefficient determination (R2) = 0,596. This matter indicate that the variation variable of product quality, price, and promotion able to explain the variation variable of consumer purchasing decision of drinking water aqua = 59,6%.